Deciphering Sustainable Development within the Framework of the International Human Rights System - ASUMU BENGO, Leticia Carmen (Strathmore Law Journal, 2022)
Today, sustainable development seems to not only have become the paradigm of new development, but its link to human rights has also become evident, considering the influence exerted on it by the main normative instruments that reflect these rights. It should come as no surprise, therefore, that this issue is now a priority within the UN’s framework for action. While traditional normative instruments such as international treaties and other conventions establish the criteria for the protection of human rights, new mechanisms, such as the Millennium Development Goals (MDGs) and the Sustainable Development Goals (SDGs) are increasingly helping to reinforce these rights as well. This paper aims to contribute in ‘deciphering’ the enigma of sustainable development, by understanding the importance of these new mechanisms, especially that of the SDGs, which are the main focus of our analysis, in order to identify their link to human rights. For this, we will provide an overview of the concept of sustainable development, analysing it from its origins in the field of international law to its current place in the Global Development Agenda. While defining the true nature of sustainable development remains a challenge, sustainable development, and more specifically the SDGs, are imbued with a human rights component.